Compósito à base de talos de girassol: uma solução de produção mais limpa para isolamento térmico - Adamy, Ana Paula do Amaral (2017)
The increase in consumption of renewable natural sources urged by the population growth and the demand for goods and services, associated with social and governamental demands towards sustainability, motivates the development of new industrial solutions that can diminish or even eradicate environmental impact created by their production processes. This research has as its goal to elaborate and distinguish a composite made form sunflower stems in order to use it as alternative material for thermal insulation. Cleaner production principles and ecodesign were used as reference, aiming to offer an option to traditionally used materials to this purpose, such as glass wool and stone wool that in addition to consuming a great quantity of energy on their manufacture, still lack on options to reclaim their useful life. The composite was a result from the mix of triturated sunflower stems with a polyurethane resin made from castor bean, used as binder. Rigid boards were manufactured with the composite. The tests indicated that the material gathers promissing characteristics for its use as a thermal insulator, presenting a thermal conductivity of 0,0928 W/mK, flexural strenght of 5,87 MPa and density of 350,59 kg/m³. In use test results exhibit a similar performance to the glass wool, used as thermal insulation on a solar collector of a water heating system for household consumption. The environmental evaluation was positive, since while on its production the goal has always been the diminishment of residues as well as the other resources. The high cost of the board compared to the glass wool one is mainly due to the high price of the resine used.